US-Elastography With Different Techniques for Thyroid Nodule Characterization: Systematic Review and Meta-analysis - Cantisani, Vito; De Silvestri, Annalisa; Scotti, Valeria; Fresilli, Daniele; Tarsitano, Maria Grazia; Polti, Giorgia; Guiban, Olga; Polito, Eleonora; Pacini, Patrizia; Durante, Cosimo; Grani, Giorgio; Isidori, Andrea M.; et al. (Frontiers in Oncology, 2022)
Background: Thyroid nodules are frequent in adult population and thyroid cancer incidence has increased dramatically over the past three decades. The aim of this systematic review (registered in the international prospective register of systematic reviews PROSPERO : CRD42021279257) and meta-analysis was to evaluate the US-Elastosonography (USE) diagnostic performance in assessing the thyroid nodules malignancy risk. Methods: PubMed and Embase databases were searched from January 2011 to July 2021. We ex-tracted data from selected studies and calculated the overall diagnostic accuracy of qualitative USE, semi-quantitative USE and quantitative USE. Summary receiver operating characteristic (ROC) curve was elaborated to show the results. All statistical tests were performed using Metadisc and Medcal software package. Results: Finally 72 studies with 13505 patients and 14015 thyroid nodules (33% malignant) un-dergoing elastography were included. The pooled sensitivity, specificity and AUC were 84%, 81% and 0.89 respectively for qualitative USE; 83%, 80% and 0.93 for semi-quantitative USE and 78%, 81% and 0.87, for quantitative USE. The qualitative and semiquantitative USE present very similar diagnostic accuracy values and both better than the quantitative USE. Conclusions: USE is a useful imaging tool for thyroid nodule characterization. In accordance with recent guidelines and meta-analyses, the USE could be used daily in thyroid nodule malignancy risk stratification.